Concomitant lithium increases radioiodine uptake and absorbed doses per administered activity in graves’ disease: comparison of conventional versus lithium-augmented radioiodine therapy - Khreish, Fadi; Schaefer-Schuler, Andrea; Roth, Leonie; Burgard, Caroline; Rosar, Florian; Ezziddin, Samer (Frontiers in Medicine, 2024)
Background Lithium inhibits iodine and thyroid hormone release from thyroid cells, possibly increasing radioiodine retention and anti-hyperthyroid efficacy when given adjunctively to radioiodine therapy (RAI) of Graves’ disease (GD). However, the literature contains limited dosimetric data regarding the influence of concomitant lithium in this setting. Methods We retrospectively compared dosimetric variables in patients undergoing RAI with/without adjunctive lithium (n = 52 each). We assessed two low-dose, short-duration oral lithium carbonate regimens, 450 mg/d (n = 22) or 900 mg/d (n = 30), for a mean of 4.7 ± 1.4 d starting upon RAI administration. Patients underwent diagnostic testing to measure thyroidal radioiodine uptake (RAIU) 24 h ± 2 h after ingesting up to 5 MBq radioiodine, receiving individualized RAI activities 24 h later. Using ≥3 RAIU daily measurements starting 24 h post-RAI, researchers were able to determine the effective radioiodine half-life and absorbed dose to the thyroid; we also calculated the absorbed dose per administered activity concentration within that organ. Rates of GD cure, defined as reaching euthyroidism or hypothyroidism post-RAI, were evaluated in patients with ~6 months or longer post-RAI follow-up. Results The lithium dosage subgroups had similar dosimetric values and thus are considered together. Lithium patients and controls had similar average “diagnostic” RAIU (51.1% ± 15.7% vs. 50.6% ± 13.8%, p = 0.820), but the former had significantly higher RAIU post-RAI (56.3% ± 13.5% vs. 49.1% ± 13.5%, p = 0.002), reflecting significantly greater change in the former (+16.2% ± 30.4% vs. -1.8% ± 16.1%, p = 0.001). Radioiodine effective half-life was non-significantly longer in lithium patients (5.43 ± 1.50 d vs. 5.08 ± 1.16 d, p = 0.192). The mean RAI administered activity was 27% less in lithium patients (677 ± 294 MBq vs. 930 ± 433 MBq, p = 0.001), but GD cure rates were similar (83% [39/47] vs. 82% [33/40], p = 0.954), possibly due to the significantly higher thyroid dose in the lithium patients, especially in thyroid gland with a volume ≤ 20 mL (1.04 ± 0.44 Gy/MBq vs. 0.76 ± 0.30 Gy/MBq, p = 0.020). Day 3 serum lithium concentrations were low (450 mg/d: 0.26 ± 0.12 mmol/L, 900 mg/d: 0.50 ± 0.18 mmol/L); no lithium toxicity was noted. Conclusion Lithium augmentation may increase the RAIU and thyroid absorbed dose, permitting potentially decreased RAI activities without sacrificing efficacy. Our observations should be confirmed in a prospective, randomized trial.